Microcoryphia (insecta) de uma floresta periodicamente inundada por água mista naamazônia central: fenologia, densidade e adaptação - Wellington de Morais, José; Adis, Joachim (Instituto de Ecología, A.C., 2008)
Most of the Microcoryphia are nocturnal that live in litter, soil cavities, on tree barks, under stones and logs. Essentially they feed on algae, lichens, plant remains and decaying fruits. In Brazil scientific information about this group of insects is scarce yet. The aim of the present work is to investigate the phenology, abundance and density of the Microcoryphia inhabiting flooded mixed-water forest in Central Amazon. Two monthly samplings with ground photo-eclectors, were carried out during the dry season (August/1987 to May/1988) to register the activity and density meanwhile weekly samplings with arboreal photo-eclectors were performed to detect vertical migration on trunks upwards anddownwards. A total of 145 individuals were captured, from which 37.2% (n=54) were collected in ground photo-eclectors and 62.8% (n=91) in arboreal photo-eclectors. The species collected were:Meinertellus adisi Sturm, 1983; Neomachilellus scandensWygodzinsky, 1978 e N. adisiWygodzinisky, 1978. N. scandens were only collected on litter and their reproduction occurred at the beginning of the dry season with post-embryonic development of approximately 40 to 50 days (from egg to sub-adult). The majority of M. adisi were immature, collected on trunks and the reproduction was plurivoltine. No vertical migration was observed during the sampling periods. We found no statistical significance between the population density of neither N. scandens of M. adisi and abiotic factors in the studied area.